Empowering Startup Supply Chain: Exploring the Integration of SCF, AI, Blockchain, and Trust - Ali Trawnih; Husam Yaseen; Malek Ahmad Alsoud; Majda Ayoub Al-Salim; Christine Hattar (Logistics, 2025)
Background: This research aims to comprehensively evaluate the influence of firm capabilities, resources, and Artificial Intelligence (AI) on supply chain financing within the Jordanian context. It also analyzes the mediating role of blockchain technology and trust in these relationships. Methods: A conceptual model was utilized to empirically examine the suggested relationships. Data were gathered from a sample of 349 Jordanian start-ups focusing on AI and blockchain technologies via a five-point Likert scale questionnaire. Partial Least Square regression-based Structural Equation Modeling (PLS-SEM) facilitated by SmartPLS4 was used to perform the analysis. Results: The findings reveal that firm capabilities/resources and AI positively impact supply chain financing. Blockchain technology and trust serve as mediators, enhancing the effects of these factors on supply chain financing. Conclusions: The study highlights the role of innovative technologies in improving financial information security and collaboration among supply chain partners. It emphasizes how firm capabilities, resources, and emerging technologies such as AI and blockchain influence supply chain financing as they foster trust and security in financial transactions, offering valuable insights for decision-makers in the supply chain domain.